Synthesis and evaluation of nitroheterocyclic aromatic adamantane amides with trypanocidal activity. Part II - Foscolos, Angeliki-Sofia; Atherton, Richard L.; Billia, Maria; Georgiadis, Markos-Orestis; Santarém, Nuno; Cordeiro-da-Silva, Anabela; Taylor, Martin C.; Kelly, John M.; Calogeropoulou, Theodora; Tsotinis, Andrew; Mavromoustakos, Thomas; Papanastasiou, Ioannis (RSC Medicinal Chemistry, 2026)
New nitroheterocyclic adamantane amides display promising trypanocidal activity. The spacer length between the adamantylphenyl backbone and the nitroheterocyclic ring plays a crucial role in potency.